Lexicultura e hipertextos : letras de canções como mediação linguística e cultural no contexto do ensinoaprendizagem de português para estrangeiros - Souza, Drielle Caroline Izaias Juvino (2015)
The integration between language and culture has acquired greater importance in the teaching and learning foreign languages context as well as in Applied Linguistics studies. Considering the lexicon as cultural depository of language (BIDERMAN, 2001), studying it becomes essential to understand and discuss the cultural aspects of a given society. In this paper we intend to analyze Brazilian lyrics that have the cultural marked lexicon in order to contribute to the discussion in the teaching-learning languages area. In addition, we present the proposal of some entries on a web site in hypertext format. We opted for the lyrics because they are an important cultural vehicle in Brazil (BARBOSA, 2008) and they allow access to both language and cultural content in foreign language classes. The virtual environment and hypertext were selected because they allow access from any location with an internet connection and propitiate dynamic reading method through navigation. We analyzed 27 Brazilian songs that cover a period of 42 years from 1972 to 2014. The focus in song analysis was the lexicon with shared cultural load, according to Galisson s conception (1987; 1989).